Analysis of the Relationship between Experience as a Facebook Content Creator and Improvement of Public Speaking Skills - Surya P, Dhika; AS, nurnisaa; Lianingsih, nestia (International Journal of Linguistics, Communication, and Broadcasting, 2024)
The abstract should summarize the context, content and conclusions of the paper in less than 200-300 words. It should not contain This study examines the relationship between content creation activities on the Facebook platform and the development of public speaking skills. Through a quantitative analysis of 120 Facebook content creators, this study investigates the correlation between content creation experience, self-confidence, and public speaking skills. The research methodology uses a survey approach with a questionnaire that includes variables such as duration of experience as a content creator, amount of content produced, level of self-confidence, and public speaking skills. The results of the Pearson correlation analysis showed that self-confidence has a very strong positive relationship with public speaking skills (r = 0.83), while the amount of content produced showed a strong correlation (r = 0.72), and experience as a content creator had a moderate correlation (r = 0.65). Linear regression analysis confirmed these findings, with self-confidence emerging as the strongest predictor (B = 0.58, p < 0.001) of public speaking skills. The age factor showed a weak correlation (r = 0.18), indicating that the development of public speaking skills through content creation is not limited by age factors.